(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
During the formation of continents some 140 million years back, few parts broke off from thethen continent of Africa drifted to the then Asian continent to form the present-day India Madagascar.The Indian peninsula was composed of old crystalline, igneous metamorphic rocks which from timeimmemorial was the seat of the world‟s richest fertile landmass. As time passed on this became the landof great civilisations. In present time, India is the world‟s 2nd most populous country with a population ofover 130 billion people spread across 29 states 5 union territories, speaking 1652 languages dialectsacross 9 major religions. Hence summing up with different cultures, geographical economicconditions gave birth to different food habits as well. India majorly an agrarian country has a populationdwindling around middle, lower middle poor mass with only ten percent of population is considered asrich. Food security to all became the major challenge to our government, who is working hard to fulfilthis demand. Also with modernisation, advancement in science industrialisation there has been steadymigration of people to these urban hubs. This gave birth to many new sectors, of which the food industryis a major part comprising of around 448 billion USD is growing at around 10 contributes to 9-10of the country‟s GDP. The retail food beverage industry of India is around 33.22 billion USD as of 2020 is expected to rise to 156.25 billion USD by 2026, growing at a CAGR of 29.88. The “In – the –Kitchen” segment of the food industry comprises of staples, spices and condiments, oil, vegetables,dairy, and others, which in turn accounts for nearly 70 of the food and beverage basket. The sad part ofthe story is marked by adulteration of food which has become the major challenge of the government.Various laws, acts measures has evolved over time to check this. An act by the name of Prevention ofFood Adulteration Act was made in 1954re modifiedin 1964, 1976 1986, to check on duplicitousprotection from adulteration contamination of food that may lead to health risk of consumers. In 2006,FCCAI (Food Safety and Standards Act of India) was formulated to bring about standards regulationsin the industry. This industry consists of various shapes sizes of food vendors out of which around100 lakh small food vendors are there in the country contributing to 2.88 lakh crore rupees daily. Thebiggest challenge is to bring them under a single platform of standards regulation due to the hugevariability present in the Indian market. This research paper investigates the different issues challenges of applicability of PFA FCCAI in bringing the small food outletsvendors under one umbrellaof standards regulations.